THE USE OF SCAFFOLDING TALK TECHNIQUE TO IMPROVE THE SECOND GRADE STUDENTS SPEAKING SKILL AT MTS MADANI PAOPAO GOWA - Fatur Rahmah; St. Nurjannah YT (ETERNAL (English, Teaching, Learning and Research Journal), 2016)
This research aimed to determine the use of scaffolding talk technique to improve the speaking skill. Therefore, the problem statement was only one, that is “Is using scaffolding talk technique effective to improve the speaking skill of the second grade students of MTs Madani PaoPao Gowa?” .The study was using quasi experimental design with non-equivalent control group design. The study involved 58 students of the second Grade students of MTs Madani PaoPao that was taken by using purposive sampling technique. The data were analyzed using descriptive statistic (frequency, mean score, and standard deviation) and inferential statistic (independent sample t-test). The result of this research showed that the mean score in the post-test for experimental class was 48.59 and for the control class was 35.52. Based on the calculation of the t-test, the result showed there was a significant difference between the mean score of both post-test. This means that scaffolding talk technique was effective to improve the students’ speaking skill. Why scaffolding talk was effective to improve the speaking skill because this technique emphasize the use of English as the language model of interaction in all learning activities in English class. Based on te result of calculation of t-test showed that the difference in the average value of the ability to speak English of both treatment groups was significant with the t-test 4.63, and the value oft-table was smaller than 2.00. These results indicate that the scaffolding talk technique is more influential in students'ability to speak English.